2001
DOI: 10.1103/physrevb.64.064301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pressure on the Raman anomaly of zinc-blende CuBr and Raman spectra of high-pressure phases

Abstract: Raman spectra of isotopically pure CuBr ( 63 Cu 81 Br) were measured under hydrostatic pressures up to 10 GPa at 10 K. The anomalous line shape of the longitudinal-optic ͑LO͒ scattering in the zinc-blende phase ͑CuBr-III, 0-4 GPa͒, consisting of a broad structure between 155 and 177 cm Ϫ1 , exhibits a continuous change with pressure and develops into a narrow LO phonon peak near 4 GPa. The disappearance of the LO Raman anomaly as well as the pronounced broadening of the TO mode with pressure are explained in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…Furthermore, with the help of ab-initio calculations we studied the pressure dependence of the Raman linewidths. For instance, we observed that the E high 2 mode exhibits a characteristic Fano-like broadening due to large phonon anharmonicities, which can be understood in terms of the pressure-tuning of a Fermi resonance, as reported for other semiconductors [14][15][16] .…”
Section: Introductionsupporting
confidence: 70%
“…Furthermore, with the help of ab-initio calculations we studied the pressure dependence of the Raman linewidths. For instance, we observed that the E high 2 mode exhibits a characteristic Fano-like broadening due to large phonon anharmonicities, which can be understood in terms of the pressure-tuning of a Fermi resonance, as reported for other semiconductors [14][15][16] .…”
Section: Introductionsupporting
confidence: 70%
“…This off-center model has been discarded rather conclusively in recent work with isotopically substituted samples. 5,6,8,9 The fact that this feature appears at high temperatures ͑see Fig. 3͒, and the low frequencies reported by inelastic neutron scattering for the transverse phonons at the zone boundaries have led us to assign this feature to two phonon difference modes.…”
Section: Discussionmentioning
confidence: 98%
“…IV B for room temperature by scaling with the temperature dependence of the different phonons in germanium. The fit procedure has been described elsewere 5,8,9,50 and yields for ͉V 3 ͉ 2 a value of Ϸ6 cm Ϫ2 . The (TAϩLA) L singularity has been enhanced ad hoc ͓dotted line in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diamond anvil cell is an excellent tool for such investigations [2] which yield detailed information about the anharmonic decay mechanisms responsible for linewidths and lineshapes. The reason for the drastic lineshape changes observed by Raman spectroscopy in CuCl [3], CuBr [4], GaP [5] and, to a lesser extent Si [6] and CuI [7] is that, in these cases, the anharmonic self-energy is determined by decay into two phonons close to Van Hove singularities at the edge of the Brillouin zone. The fact that the corresponding two-phonon density of states (DOS) has strong singularities near Raman LO (CuBr) or TO (CuCl, GaP) phonons, together with strong anharmonic coupling constants, gives rise to complex lineshapes which are determined not only by the imaginary part but also by the real part of the selfenergy.…”
mentioning
confidence: 94%